5x+1-11=0

Add 11 to both sides of the equation.

5x+1=11

To remove the radical on the left side of the equation, square both sides of the equation.

5x+12=112

Multiply the exponents in ((5x+1)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(5x+1)12⋅2=112

Cancel the common factor of 2.

Cancel the common factor.

(5x+1)12⋅2=112

Rewrite the expression.

(5x+1)1=112

(5x+1)1=112

(5x+1)1=112

Simplify.

5x+1=112

Raise 11 to the power of 2.

5x+1=121

5x+1=121

Move all terms not containing x to the right side of the equation.

Subtract 1 from both sides of the equation.

5x=121-1

Subtract 1 from 121.

5x=120

5x=120

Divide each term by 5 and simplify.

Divide each term in 5x=120 by 5.

5×5=1205

Cancel the common factor of 5.

Cancel the common factor.

5×5=1205

Divide x by 1.

x=1205

x=1205

Divide 120 by 5.

x=24

x=24

x=24

Solve for x square root of 5x+1-11=0